PERANCANGAN SISTEM INFORMASI PENGOLAHAN DATA PEGAWAI BERBASIS WEB: WEB-BASED EMPLOYEE DATA PROCESSING INFORMATION SYSTEM DESIGN - David Saro; Muhammad Noreza Setiawan (Engineering and Technology International Journal, 2020)
At SDIT Darul Falah, a private elementary school in Nongsa sub-district, Batam City, this school has approximately 40 temporary employees. So far, in the process of processing employee data, employees are still using Microsoft office excel, to obtain or edit employee data, they must meet the section that manages the data. , so it occurred to me to design a system that can facilitate the performance of employees. The design is done by using ERD to model the data and processes. With this system, it is hoped that it will facilitate the processing of employee